Exploring Gst Efficiency In India: The Interplay Of Trust, Technology, And Compliance Dynamics - Rani, J. Hena Esther; Kalpana, G.; Jagadeesan, P. (Journal of Neonatal Surgery, 2025)
This paper examined the effectiveness of India’s GST system, focusing on the dynamics of compliance, technology, and trust since the system's introduction in 2017. This study highlights the persistent problems that impact compliance cost and taxpayer confidence, including policy changes, technical difficulties, and intergovernmental conflicts. By examining the connections between the dependent variable, the effectiveness of the GST system, and factors such as governance trust, digital literacy, adaptive compliance behaviour, and perception of decentralisation, quantitative data were collected. Key stakeholders were interviewed, and GST-registered taxpayers were surveyed. By examining the connections between the dependent variable, the effectiveness of the GST system, and factors such as governance trust, digital literacy, adaptive compliance behaviour, and perceptions of decentralisation, quantitative data were collected. Key stakeholders were interviewed, and 300 GST-registered taxpayers were surveyed. The results show that digital literacy (r = 0.802) and adaptive compliance behaviour (r = 0.782) are strongly positively correlated with the efficiency of the GST system. Governance trust exhibited a moderate correlation (r = 0.602), whereas decentralisation perception also demonstrated a significant positive correlation (r = 0.610). All predictor variables have a positive impact on the efficiency of the GST system, according to regression analysis, with digital literacy being the most important component. The conclusion highlights how crucial digital infrastructure and user expertise are to improving GST efficiency, as well as how crucial flexible compliance practices and decentralisation attitudes are to promoting efficient tax administration.